Three-dimensional Planning and Simulation of Hip Operations and Computer-Assisted Design of Endoprostheses in Bone Tumor Surgery - Heinz Handels; Jan Ehrhardt; Plötz, W; Siegfried J. Pöppl (Computer aided surgery : official journal of the International Society for Computer Aided Surgery, 2001)
OBJECTIVE: This article presents the VIRTOPS (VIRTual Operation Planning in Orthopaedic Surgery) software system for virtual preoperative planning and simulation of hip operations. The system is applied to simulate the endoprosthetic reconstruction of the hip joint with hemipelvic replacement, and supports the individual design of anatomically adaptable, modular prostheses in bone tumor surgery. The virtual planning of the operation and the construction of the individual implant are supported by virtual reality techniques. The central step of the operation planning procedure, the placement of the cutting plane in the hip bone, depends strongly on the tumor's position. Segmentation of the tumor and the bones in MR and CT data, as well as fusion of MR and CT image sequences, is necessary to visualize the tumor's position within the hip bone. MATERIALS AND METHODS: Three-dimensional models of the patient's hip are generated based on CT image data. A ROI-based segmentation algorithm enables the separation of the bone tumor in multispectral MR image sequences. A special registration method using segmentation results has been developed to transfer CT and MR data into one common coordinate system. During the 3D planning process, the surgeon simulates the operation and defines the position and geometry of the custom-made endoprosthesis. Stereoscopic visualization and 3D input devices facilitate navigation and 3D interaction in the virtual environment. Special visualization techniques such as texture mapping, color coding of quantitative parameters, and transparency support the determination of the correct position and geometry of the prosthesis. RESULTS AND CONCLUSIONS: The VIRTOPS system enables the complete virtual planning of hip operations with endoprosthetic reconstruction, as well as the optimal placement and design of endoprostheses. After the registration and segmentation of CT and MR data, 3D visualizations of the tumor within the bone are generated to support the surgeon during the planning procedure. In the virtual planning environment, individually adapted endoprostheses can be constructed without the need to generate expensive solid 3D models. Furthermore, different operation strategies can be compared easily. Three-dimensional images and digital movies generated during the virtual operation planning can be used for case documentation and patient information purposes.
Keywords: Algorithms; Arthroplasty, Replacement, Hip; Bone Neoplasms; Hip Joint; Humans; Imaging, Three-Dimensional; Software; Therapy, Computer-Assisted